2009
DOI: 10.1049/iet-epa.2008.0248
|View full text |Cite
|
Sign up to set email alerts
|

Effect of loading, voltage difference and phase angle on the synchronisation of a small alternator

Abstract: Synchronisation of small distributed generation, 30 kVA -2 MVA, employing salient-pole synchronous machines is normally performed within a narrow range of tolerances for voltage, frequency and phase angle. However, there are situations when the ability to synchronise with non-ideal conditions would be beneficial. Such applications include power system islanding and rapid generator start-up. The physical process and effect of out-of-phase synchronisation is investigated both through simulation and experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
1
7
0
1
Order By: Relevance
“…If the phase‐drift is less than the threshold ± θ a , then it is safe to reclose. The author's have previously shown an out‐of‐phase reclose of ±60° is within the transient torque and current limits for a synchronous machine [25, 26], but would not recommend such a large out‐of‐phase reclosure as common practice. A much smaller threshold is recommended in Section 5.…”
Section: Synchrophasor Loss‐of‐mains Detectormentioning
confidence: 99%
See 1 more Smart Citation
“…If the phase‐drift is less than the threshold ± θ a , then it is safe to reclose. The author's have previously shown an out‐of‐phase reclose of ±60° is within the transient torque and current limits for a synchronous machine [25, 26], but would not recommend such a large out‐of‐phase reclosure as common practice. A much smaller threshold is recommended in Section 5.…”
Section: Synchrophasor Loss‐of‐mains Detectormentioning
confidence: 99%
“…A much smaller threshold is recommended in Section 5. Detection time for out‐of‐phase reclosure is thus effectively zero seconds, since as the authors show in [25, 26], an embedded generator could be reclosed without damage even after the synchrophasor loss‐of‐mains has indicated an island has formed.…”
Section: Synchrophasor Loss‐of‐mains Detectormentioning
confidence: 99%
“…1(c), (d) and (e). The loaded short-circuit is a design constraint for larger synchronous machines [15], and out-of-phase synchronisations are of interest as they can be more severe for the machine than any other event [4,16,17]. Thus it is of benefit to understand the physical process during these events.…”
Section: Current Componentsmentioning
confidence: 99%
“…The worldwide installed capacity of distributed generation is increasing and an interest in islanding of distribution networks [1,2,3] has prompted the authors to review the out-of-phase synchronisation and fault characteristics of small alternators. Related work by the authors [4], concentrating on peak current and torque, has indicated that the synchronisation angle limits of salient-pole alternators could be increased 2 significantly beyond the current narrow range of tolerances stipulated in IEEE 1547 [5] and ETR 113 [6].…”
Section: Introductionmentioning
confidence: 99%
“…The results indicate that with a sophisticated governor and suitable communications structure, this is indeed feasible in the single-set case. Experimental work was also performed to determine suitable boundaries within which to control the phase angle [10]. A range of ±60° was proposed, this being no worse than a sudden three phase short-circuit, which the DG is designed to withstand, and is a significantly wider window than current synchronization schemes operate with [11,12].…”
Section: Introductionmentioning
confidence: 99%